Introduction to statistics and data analysis - Peck, Roxy; Devore, Jay L.; Olsen, Chris (Brooks/Cole, Cengage Learning, 2012)
Uses real data and examples to introduce students to the study of statistics and data analysis. This book guides students through an intuition-based learning process that stresses interpretation and communication of statistical information. It includes coverage of the graphing calculator as well as expanded coverage of probability.